Impact of Rewards (Intrinsic and extrinsic) on Employee Performance With Special Reference to Courier Companies of City Faisalabad, Pakistan. - Khan, Nosheen; Waqas, Hafiz; Muneer, Rizwan (International Journal of Management Excellence (ISSN: 2292-1648), 2017)
The study has conducted to measure the effect of rewards (Intrinsic & Extrinsic) on employee job performance. The experiences and personal opinions of employees working in different couriers companies were analyzed through questionnaires in the city of Faisalabad. The key objective of the study was to find that the rewards affect the performance of an employee. Statistical package (SPSS) has been used to conduct the analysis of the study. Employees like Field Supervisors, Couriers from selected courier companies (TCS, OCS, Leopard and Express Courier Services) were randomly chosen. The focus of the study was to distribute and highlight an adequate level of incentives to the employees and create balance in distribution of rewards so that every employee contributes his efforts for the growth of the company. This study also focuses on two major rewards, intrinsic and extrinsic rewards. Rewards plays a motivational role in the personality of an employee and urge them to produce loyalty and show good performance By the results study shows that there is a strong relationship between both type of rewards and on employee performance. Concluding, the study has verified and explores further research opportunities that can enhance the understanding of rewards and employees job performance. Keywords: Intrinsic Rewards, Extrinsic Rewards, Job Performance, TCS, OCS, Leopard & Express Couriers.